A Novel Human Tissue-Engineered 3-D Functional Vascularized Cardiac Muscle Construct - Valarmathi, Mani T.; Fuseler, John W.; Davis, Jeffrey M.; Price, Robert L. (Frontiers in Cell and Developmental Biology, 2017)
Organ tissue engineering, including cardiovascular tissues, has been an area of intense investigation. The major challenge to these approaches has been the inability to vascularize and perfuse the in vitro engineered tissue constructs. Attempts to provide oxygen and nutrients to the cells contained in the biomaterial constructs have had varying degrees of success. The aim of this current study is to develop a three-dimensional (3-D) model of vascularized cardiac tissue to examine the concurrent temporal and spatial regulation of cardiomyogenesis in the context of postnatal de novo vasculogenesis during stem cell cardiac regeneration. In order to achieve the above aim, we have developed an in vitro 3-D functional vascularized cardiac muscle construct using human induced pluripotent stem cell-derived embryonic cardiac myocytes (hiPSC-ECMs) and human mesenchymal stem cells (hMSCs). First, to generate the prevascularized scaffold, human cardiac microvascular endothelial cells (hCMVECs) and hMSCs were co-cultured onto a 3-D collagen cell carrier (CCC) for 7 days under vasculogenic culture conditions. In this milieu, hCMVECs/hMSCs underwent maturation, differentiation, and morphogenesis characteristic of microvessels, and formed extensive plexuses of vascular networks. Next, the hiPSC-ECMs and hMSCs were co-cultured onto this generated prevascularized CCCs for further 7 or 14 days in myogenic culture conditions. Finally, the vascular and cardiac phenotypic inductions were analyzed at the morphological, immunological, biochemical, molecular, and functional levels. Expression and functional analyses of the differentiated cells revealed neo-angiogenesis and neo-cardiomyogenesis. Thus, our unique 3-D co-culture system provided us the apt in vitro functional vascularized 3-D cardiac patch that can be utilized for cellular cardiomyoplasty.